Social Values and Knowledge Predict Attitudes within an Urban Protected Area in El Salvador. Issue 4 (3rd April 2022) - Carr, Bradley; van Riper, Carena J.; Miller, Daniel C.; Hodson, Piper; Eriksson, Max
Abstract: Urban protected areas are faced with numerous pressures from intensified land uses that jeopardize their sustainability, particularly in Central America where there is an abundance of areas managed for conservation yet limited financing. An understanding of the factors that influence public support for fee programs is of paramount importance but difficult to anticipate without empirical evidence of the social phenomena that influence attitudes. Here, we used on-site survey data to understand the relationships among the perceived benefits of nature (i.e., social values), knowledge and attitudes toward a proposed increase in fees to enter an urban protected area in El Salvador, the El Espino forest reserve. Our results revealed an array of reasons why visitors valued places, particularly aesthetics, opportunities for recreation, life sustaining qualities, biodiversity, and the intrinsic qualities of nature. As these social values increased, so too did support for user fees. Knowledge about environmental, social, and management conditions of the protected area was also instrumental in explaining why a range of social values and attitudes were expressed by respondents. These results provide insights on how to increase support for a fee program that could enhance management of the El Espino reserve with broader implications for other urban protected areas in the region and beyond.